2017
DOI: 10.1177/0047287517705225
|View full text |Cite
|
Sign up to set email alerts
|

Is Xenios Zeus Still Alive? Destination Image of Athens in the Years of Recession

Abstract: This study examines the evolution of the city of Athens’ destination image from 2005 to 2015, in order to exploit the impact of the recent economic recession on individual perceptions. It uses advanced web content mining to analyze Tripadvisor messages that were posted in Athens Travel Forum. The findings show that the image of Athens has remained positive, facing a significant, but short-term, shift during the first years of the crisis. The findings also reveal that the destination image of Athens is only par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 75 publications
5
24
0
1
Order By: Relevance
“…According to a recent study [100], Attica stands out for its attractions classified as ancient ruins. Overall, the image of Attica is very positive (Table 6), coinciding with a previous study on the TDI of Athens during the recession years [21].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…According to a recent study [100], Attica stands out for its attractions classified as ancient ruins. Overall, the image of Attica is very positive (Table 6), coinciding with a previous study on the TDI of Athens during the recession years [21].…”
Section: Discussionsupporting
confidence: 89%
“…A study focused on exploring similarities between attractions through 1,695,333 OTRs that highlighted Athens, Cairo and Rome in the category of ancient ruins deserves special attention [100]. As subsequent research has shown, people who use reviews of various tourism products have particular objectives, including opinion mining [101], especially for information about tourist satisfaction [102] and affective image [21]. Recent research based on 25,220 TripAdvisor reviews on things to do in an Italian province [103] is not focused on TDI, but it measures visitor satisfaction through its evaluation that uses between one and five bubbles and implements a content analysis using the commercial application Leximancer.…”
Section: Use Of Big Data Analytics In Hospitality and Tourism Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…After the vacation and the tourist's personal experience, a final image is generated. For Um and Crompton (1990) and Ugarte (2007), the perceived image of a place will be formed by the interaction of the projected image (the destination image the promotional information projects) and the individual's needs, motivations, experience, preferences and personal characteristics, and this image is very resistant to change, even in times of economic crisis (Gkritzali et al, 2018). Thus, we propose the following hypotheses: Overall satisfaction with the vacation is a very interesting variable, because, depending on the level of satisfaction or dissatisfaction, the degree of tourist loyalty to both the geographical area and the accommodation can be calculated.…”
Section: Research Hypothesismentioning
confidence: 99%
“…It has further been recognized that destinations which invest in a wrong image are likely to "lose" their competitive position in the future (Avraham, 2004). A plethora of studies have explored the content of destination image by assessing visitors' and/or potential visitors' perceptions of place-specific attributes, such as scenery, attractions, climate and friendliness of the locals (Iordanova and Stylidis, 2017;Gkritzali et al, 2017;Stepchenkova and Li, 2014). However, very few studies have focused on understanding the characteristics (i.e.…”
Section: Introductionmentioning
confidence: 99%